Membangun Kesadaran Spiritual dalam Era Modern - Gelgel, I Putu (Kajian dan Reviu Jinarakkhita: Jurnal Gerakan Semangat Buddhayana (Jinarakkhita Review & Studies: Journal of Buddhayana Spirit Movement), 2025)
In the modern era, marked by technological advancements, globalization, and increasing life pressures, human beings often experience a disorientation of values and a loss of life’s meaning. Progress in science and technology has indeed made life easier, but it has also brought negative effects such as stress, anxiety, social alienation, and existential crises. In such circumstances, spiritual awareness becomes essential as a tool to balance the inner needs of human beings with worldly achievements. Spiritual awareness is not only related to religion, but also encompasses human relationships with noble values such as compassion, peace, self-awareness, and a deeper sense of meaning in life. It is closely connected with the awareness of life’s purpose and the relationship with something greater than oneself. Cultivating spiritual awareness helps individuals become more reflective, more resilient to stress, and more caring toward others.